Impacts of the aneurysm deformation induced by stent on hemodynamic of blood flow in saccular internal carotid artery aneurysms - S. Valiallah Mousavi; Mostafa Barzegar Gerdroodbary; Amir Sabernaeemi; Sajad Salavatidezfouli; Peiman Valipour (AIP Advances, 2024)
Recognition of the aneurysm rupture risk after endovascular treatments is important for the evaluation of the applied treatment technique. In this paper, the role of the stent in the treatment of saccular internal carotid artery (ICA) aneurysm patients has been investigated to assess the performance of this endovascular technique in the reduction of bleeding possibility and hemorrhage. Hemodynamic studies have been performed to compare the main effective factors of wall shear stress, oscillatory index, and pressure on the aneurysm wall in different stages of the cardiac cycle. The computational technique of finite volume is used to model the pulsatile blood flow inside three different ICA patients. To simulate blood flow, the one-way fluid–solid interaction technique is considered for the interaction of the blood and vessel, and the Casson non-Newtonian model is applied for the modeling of the blood viscosity. The comparison of the velocity magnitude of deformed cases with the original also shows how the blood flow is limited by the deformation of the aneurysms. Aneurysm deformation induced by the stent reduces the blood flow rate into the sac section, and consequently, wall shear stress is decreased on the surface of aneurysms. Stent-induced straightening of the vessel shows superior performance in hemodynamic changes and could lower recurrence rates, while stenting may have negative impacts on hemodynamic alterations.